The Role of Diabetes Mellitus Panel on Kidney Function Decline in Elderly Population: Cross-Sectional Study - Shirly Gunawan; Robert Kosasih; Yohanes Firmansyah; Alexander Halim Santoso; Bryan Anna Wijaya; Kresna Bambang; Farhan Pratomo (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Chronic kidney disease (CKD) is a major public health issue, particularly among the elderly, where metabolic disturbances accelerate renal decline. Diabetes mellitus contributes to kidney dysfunction through insulin resistance and altered glycemic control. This study investigates the relationship between diabetes-related parameters—fasting blood glucose, HbA1c, fasting insulin, HOMA-IR, and kidney function, as measured by estimated glomerular filtration rate (eGFR) in an elderly population. Methods. A cross-sectional analytic study was conducted among 82 elderly residents of Bina Bhakti Nursing Home. Venous blood samples were collected to assess fasting blood glucose, HbA1c, fasting insulin, and HOMA-IR. Kidney function was estimated using the CKD-EPI equation. Results. Age showed a significant negative correlation with eGFR (r = –0.266, p = 0.016), indicating age-related renal decline. HOMA-IR (r = 0.247, p = 0.025) and fasting insulin (r = 0.224, p = 0.043) demonstrated weak but significant positive correlations with eGFR. Conversely, fasting glucose (r = 0.055, p = 0.623) and HbA1c (r = 0.029, p = 0.795) had negligible, non-significant correlations with eGFR, suggesting limited predictive value for renal impairment. Insulin growth factor exhibited a weak, non-significant negative correlation (r = –0.104, p = 0.355). Conclusion. Age remains a key determinant of declining kidney function in the elderly. Insulin resistance markers showed mild but unexpected associations, warranting further longitudinal studies to confirm these findings and explore underlying mechanisms.